2020
DOI: 10.1515/med-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

SLC12A8 plays a key role in bladder cancer progression and EMT

Abstract: Bladder cancer is the most common malignant tumor of the urinary system. The intention of the present research is to explore the prognostic value and biological function of solute carrier family 12 member 8 (SLC12A8) in bladder cancer. The analysis based on the TCGA and ONCOMINE database revealed that the expression of SLC12A8 in bladder cancer was notably increased compared with the normal group. SLC12A8 expression was notably correlated with the age, pathological stage, T-stage, and lymph node metastasis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Studies have also found that NKCC1 is related to interneurons in the brain ( 39 , 40 ) and plays a certain role in controlling epilepsy ( 38 , 41 ). The regulatory role of solute carrier family 12 members in tumor progression and immune responses has been rarely reported, and recent studies have found that SLC12A8 plays a critical role in bladder cancer progression and EMT ( 42 ). Some new studies believe that NKCC1 is an essential ion cotransporter in the progression of glioma ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found that NKCC1 is related to interneurons in the brain ( 39 , 40 ) and plays a certain role in controlling epilepsy ( 38 , 41 ). The regulatory role of solute carrier family 12 members in tumor progression and immune responses has been rarely reported, and recent studies have found that SLC12A8 plays a critical role in bladder cancer progression and EMT ( 42 ). Some new studies believe that NKCC1 is an essential ion cotransporter in the progression of glioma ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…SLC12A8 and SLC47A1 belong to solute carrier families which regulate the transport of metal-containing anticancer drugs. It was proved that SLC12A8 overexpression could promote cell migration and invasion and may contribute positively to EMT and tumor metastasis [42]. For SLC47A1 (MATE1), recent research found that silence of MATE1 triggered by KRAS mutation could enhance intracellular metformin concentration and improve survival in metastatic colorectal cancer patients, which indicates targeting MATE1 may improve the therapeutic effect of metformin [43].…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistical difference in the clinical variables between the primary cohort and internal validation cohort. Among all BLCA patients receiving RC, the median ELN, NLN and LONT count (IQR) were 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), 13 (7-23) and 0.7 (0.5-1.0), respectively. The majority of them were between 63 and 76 years old (44.6%), male (66.7%), white (86.8%) and married (61.1%).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In fact, the T stage is a powerful risk factor for BLCA and represents the major tumor features. An increasing number of studies have suggested that T stage is closely associated with prognosis and tumor biological features (13)(14)(15). T stage can represent the biological characteristics of tumor.…”
Section: Introductionmentioning
confidence: 99%